# Find what the given equation becomes when the origin is shifted to the point (1, 1).xy – x – y + 1 = 0

Let the new origin be (h, k) = (1, 1)

Then, the transformation formula become:

x = X + 1 and y = Y + 1

Substituting the value of x and y in the given equation, we get

xy – x – y + 1 = 0

Thus,

(X + 1)(Y + 1) – (X + 1) – (Y + 1) + 1 = 0

XY + X + Y + 1 – X – 1 – Y – 1 + 1 = 0

XY = 0

Hence, the transformed equation is XY = 0

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Various Forms of Equations of line45 mins
Slope, inclination and angle between two lines48 mins
Interactive Quiz on Equations of line23 mins
Straight line | Analyse your learning through quiz56 mins
Parametric Equations of Straight line48 mins
General Equation of a line43 mins
Motion in a Straight Line - 0372 mins
Motion in a Straight Line - 0665 mins
Motion in a Straight Line - 0556 mins
Motion in a Straight Line - 0152 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses